DIGITAL COMMUNICATION AND PERSUASION OF HEALTH PROMOTIONS ON INSTAGRAM: PREVENTIVE ACTION FROM STUNTING - Daniel Susilo; Harliantara (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2023)
Stunting is actually the main matter that Indonesia will face in the future. Indonesia had suffered great crisis in the Suharto era, hence so many people breed children without thinking how to feed them nor giving them proper education. This doesn’t count the conflict of wealth shared between families led into more homeless family. Today, due to numerous ignored cases, Indonesia finally joins hand to prevent Stunting from dominating Indonesia. However, as we get informative and professional media for that, we also experience the digital disruption created by political buzzer. This makes the reality be clearer that government decision is connected to their election.